Create Domain-Specific Language and Syntax Checker Using Xtext - Billy Jonathan; Rafayel Avetyan; Stan Abeln (Institute of Research and Community Outreach - Petra Christian University, 2020)
ASML is a company that manufactures the TWINSCAN machine that can produce semiconductor chips. This machine has a TWINSCAN software installed inside it and that software needs mapping configuration files to keep it running properly. The configuration files are developed by developers from many departments within ASML. However, the development process of the configuration files is ineffective, as the developers will know if there is any defect in the source code only in the late part of the development after all files have been committed into the TWINSCAN software’s source code archive. It would be better if the developers know if there is any invalid syntax in the configuration files when they are still creating or editing the files, so they can fix the defects immediately before the files are uploaded into the source code archive. The main purpose of this research is to develop a Domain-Specific Language (DSL) based on the structure of the configuration files, and a syntax checker application that can check the mapping configuration files for the TWINSCAN machine during the creation or editing phase of those files by the developers. The development of the DSL and syntax checker would be done using Xtext framework installed in Eclipse Integrated Development Environment (IDE). The final results show that the DSL and the syntax checker developed using Xtext can detect any invalid syntax during the development phase of the configuration files, so the developers can fix the defects directly, thus solving the company’s problem.